Pemanfaatan Media Sosial sebagai Alat Promosi pada Usaha Tourist Information Center - Ni Putu Yesi Krisna Dewi; Fransiska Regista Hadan; Ni Wayan Pranindyastami; Ni Komang Rika Trianthi; Ni Putu Candra Oktavianti; Ni Ketut Abellia Kusumastuti; Made Satria Pramanda Putra (JURNAL AKADEMISI VOKASI, 2025)
This study examines the use of social media by the Tourist Information center (TIC), a local tourism service business operating in the Legian and Seminyak areas of Bali. Social media has proven effective in strengthening destination image through visual content, user testimonials, and two way interaction. However, in practice, TIC still faces several challenges, including limited human resources, advertising costs that are not proportional to outcomes, and inconsistent digital identity. This research employs a descriptive qualitative approach using in depth interviews, social media observation, and literature review. The findings reveal that strategies based on traveler experiences, the integration of digital service links, and content alignment with digital trends help build trust and increase audience engagement. This study provides practical insights for small tourism businesses in designing impactful digital promotion strategies and offers a conceptual foundation for understanding the role of social media in local tourism enterprises. Keywords: Social Media, Tourism Promotion, and Digital Strategy.